Инновационные подходы при расчете лизинговых платежей в операционном лизинге (Путеводитель предпринимателя, 2020)
In given article process of creation of an innovative design procedure of leasing payments at operational leasing in detail reveals. The problem of creation of the special mechanism of calculation of leasing payment has been put and solved at the operational form of the leasing which is based on changed a way of charge of amortization on the sum of numbers of years, taking into account reception in the end of term of leasing of real market residual cost of leasing property.